Progress on Thin Film Freezing Technology for Dry Powder Inhalation Formulations - Sagar R. Pardeshi; Eknath B. Kole; Harshad S. Kapare; Sachin M. Chandankar; Prashant J. Shinde; Ganesh S. Boisa; Sanjana S. Salgaonkar; Prabhanjan S. Giram; Mahesh P. More; Praveen Kolimi; Dinesh Nyavanandi; Sathish Dyawanapelly; et al. (MDPI AG, 2022)
The surface drying process is an important technology in the pharmaceutical, biomedical, and food industries. The final stage of formulation development (i.e., the drying process) faces several challenges, and overall mastering depends on the end step. The advent of new emerging technologies paved the way for commercialization. Thin film freezing (TFF) is a new emerging freeze-drying technique available for various treatment modalities in drug delivery. TFF has now been used for the commercialization of pharmaceuticals, food, and biopharmaceutical products. The present review highlights the fundamentals of TFF along with modulated techniques used for drying pharmaceuticals and biopharmaceuticals. Furthermore, we have covered various therapeutic applications of TFF technology in the development of nanoformulations, dry powder for inhalations and vaccines. TFF holds promise in delivering therapeutics for lung diseases such as fungal infection, bacterial infection, lung dysfunction, and pneumonia.